Toxoplasma gondii infection in wild boars (Sus scrofa) bred in Brazil - Fornazari, Felipe [UNESP]; Langoni, Hélio [UNESP]; da Silva, Rodrigo Costa [UNESP]; Guazzelli, Alessandro [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Chiacchio, Simone Biagio [UNESP] (Elsevier B.V., 2009)
Domestic pigs are considered to be important sources of Toxoplasma gondii infection for humans. Due to the increased consumption of wild boar meat in Brazil, this species may also be an important source of the parasite. The objective of the present study was to detect T. gondii infection in 306 blood samples collected from wild boars bred in the state of São Paulo, Brazil. Samples were analyzed using the modified agglutination test (MAT), and 14 (4.5%) of them yielded positive results. Modern breeding techniques may have contributed to the low frequency of infection observed. Results indicated that wild boars were exposed to T. gondii and that the consumption of this kind of meat may represent a source of infection for humans. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; Wild boar; Sus scrofa; Zoonosis